PENGOLAHAN KRISPY BANDENG DAN BANDENG PRESTO UNTUK PENINGKATAN EKONOMI RUMAH TANGGA DI KECAMATAN BINAMU - Hadijah, Siti; Ibrahim, Bachtiar (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2023)
Jeneponto Regency is known as a producer of nener and milkfish fry which are widely cultivated in South Sulawesi. In 2007 the production of milkfish fry produced was 8529 (thousands of heads) while nener was 10615 (thousands of heads). In 2008, it succeeded in producing milkfish through pond cultivation amounting to 2,904 tons. This potential provides an opportunity for the Jeneponto community to develop the processing of fishery products, especially milkfish, in order to increase their income. Binamu Subdistrict as one of the sub-districts in Jeneponto has the potential to develop milkfish processing into krispy bandeng and presto milkfish. The purpose of this program is to reactivate the activities of the group of housewives in order to improve the family economy. This PKM program will be implemented for approximately eight months, from May to December 2014 in Balang Toa Village and Pa'biringa Village, Binamu District, Jeneponto Regency, South Sulawesi. The method used provides training and mentoring to partner groups. Group determination using purposive sampling method, namely the Lestari group in Balang Toa Village and the Cahaya group in Pa'biringa Village. The results of the activity can reactivate the group of housewives, and be able to produce krispy milkfish and presto milkfish until finally they can be marketed around their homes.